Incidence and Outcomes of Radial Artery Loop in Patient Undergoing Coronary Angiography - Khan, Farhat Ullah; Khan, Tashfeen Irtaza; Parvez, Muzdalfa; Musa, Muhammad; Khan, Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Objective: The primary objective of this study was to determine the incidence and outcomes of radial artery loops in patients undergoing coronary angiography (CAG) at Hayatabad Medical Complex, Peshawar, focusing on procedural time, complications, recovery time, radial artery occlusion, and procedural success. Methodology: This retrospective study included 150 patients, divided into two groups: 75 patients with radial artery loops and 75 with normal radial anatomy. Data were collected from patient records between January 2023 and December 2023. Procedural outcomes, complications, and recovery were analyzed, and statistical comparisons were made using t-tests. Results: The average procedure time for the "Normal Radial Artery" group was 76.93 minutes, while in the "Radial Artery Loop" group, it was 73.25 minutes (p = 0.39). Post-procedural complications occurred in 53.3% of the normal group and 45.3% in the loop group (p = 0.62). Recovery time was 7.53 days in the normal group and 7.85 days in the loop group (p = 0.62). Radial artery occlusion rates were 49.3% for the normal group and 56.0% for the loop group (p = 0.62). Procedural success rates were 49.3% for the normal group and 53.3% for the loop group (p = 0.62). Conclusion: The presence of radial artery loops does not significantly affect the procedural outcomes of CAG, including procedural time, complications, recovery, and success rates. The study provides valuable insights for managing radial artery loops in clinical practice.